2018
DOI: 10.2478/foecol-2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

The influence of forest-forming tree species on diversity and spatial distribution of algae in forest litter

Abstract: The forest litter plays a significant role in forest ecosystems. The composition of the litter biota comprises micro- and mesofauna, and a great diversity of microorganisms, including unrecognized algae (eukaryotic representatives and Cyanoprokaryota). The aim of this work was to study the diversity of algae in the different types of forest litters and to clarify the relationship between the algae composition and the forest-forming tree species. Our results show that the pine forest litter is the most appropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 38 publications
0
8
0
1
Order By: Relevance
“…Accordingly, microalgae are adapted to various lighting conditions. There are species that are found in highly shaded habitats, for example, in the soil under the dense canopy of higher plants [25,26], above-water and underwater caves, in deep water layers [27][28][29]. Other species are adapted to growth in direct sunlight, for example, in polar, tropical deserts [30][31][32], on salt marshes and other open surfaces [33][34][35][36], where the light intensity can reach 2000 µmol photons m −2 s −1 [15].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, microalgae are adapted to various lighting conditions. There are species that are found in highly shaded habitats, for example, in the soil under the dense canopy of higher plants [25,26], above-water and underwater caves, in deep water layers [27][28][29]. Other species are adapted to growth in direct sunlight, for example, in polar, tropical deserts [30][31][32], on salt marshes and other open surfaces [33][34][35][36], where the light intensity can reach 2000 µmol photons m −2 s −1 [15].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the diversity of representatives of the genus Hantzschia among soil diatoms was reported as H. abundans Lange-Bertalot, H. amphioxys , H. elongata Grunow and H. vivax (W. Smith) Peragallo, including some of their varieties 26 – 34 . H. amphioxys , as the most commonly reported species, has been noted to occur in various ecosystems, from diverse soils, including alkaline 32 or calcareous 26 , soils of halophilic, shrub, meadow, and psammophytic phytocenoses 30 , soil horizons in artificial and natural forests of the steppe zone 33 , 35 , forest litter of pine, oak and white acacia plantations 36 , urban soils 37 and disturbed lands 38 . It was shown that H. amphioxys could dominate even in the steppe soil post-pyrogenic communities 39 and in biological soil crusts after the effects of fire 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Anthropogenic impacts alter the structural development of urban forests, affecting both positively through the formation of gaps, the appearance of deadwood, and the formation of ecosystem complexity, and negatively through the shifts in composition and successional trajectories (Alasmary et al, 2020;Matsala et al, 2021). Plants are an important component of landscape design (Maltsev & Maltseva, 2018;Goncharenko & Yatsenko, 2020). They perform a number of functions in a holistic landscape (Maltseva et al, 2017).…”
Section: Introductionmentioning
confidence: 99%